2013
DOI: 10.5740/jaoacint.11-080
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatographic Determination of Memantine in Human Urine Following Solid-Phase Extraction and Precolumn Derivatization

Abstract: A validated HPLC-UV method is presented for the quantification of urinary memantine hydrochloride, a novel medication approved to treat moderate and advanced cases of Alzheimer's disease. The drug and amantadine hydrochloride, the internal standard, were extracted from human urine using SPE. The extract was then buffered and derivatized at room temperature using o-phthalaldehyde in the presence of N-acetyl-L-cyteine. Chromatographic separation of the formed derivatives was achieved on a C18 column using methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…[5] Several high-performance liquid chromatography (HPLC) methods have been reported in combination with ultraviolet or fluorescence detection, but these invariably had involved pre-column or post-column derivatization. [6][7][8][9][10][11][12][13][14][15] A few gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry methods have also been reported for quantitation of the drug in biological fluids. [9,[14][15][16][17] Unfortunately, most of them have also involved tedious extraction procedures and even derivatization.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Several high-performance liquid chromatography (HPLC) methods have been reported in combination with ultraviolet or fluorescence detection, but these invariably had involved pre-column or post-column derivatization. [6][7][8][9][10][11][12][13][14][15] A few gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry methods have also been reported for quantitation of the drug in biological fluids. [9,[14][15][16][17] Unfortunately, most of them have also involved tedious extraction procedures and even derivatization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the derivatization reaction process of FDNB was more complex, because FDNB is required for an additional process to hydrolyze to dinitrophenol in the acidic conditions, compared to our UV-HPLC method with FMOC derivatization. In addition, although Michail et al (2013) also recently founded a sensitive UV-HPLC method using o-phthalaldehyde in the presence of N-acetyl-L-cystein, tedious sample preparations of solid-phase extraction were still required with a limited application of human urine sample. Again, our developed UV-method with FMOC derivatization is quite simple and effective to be capable of UV detection of the drug, especially for in vitro dissolution samples of memantine hydrochloride.…”
Section: Stabilitymentioning
confidence: 99%
“…So far, it has been reported that memantine was subjected to be pre-derivatized with some reagents including 9-fluorenylmethyl-chloroformate (FMOC) and dansyl chloride etc. in order to be readily detected for UV- (Narola et al 2010;Haen et al 2012;Jalalizadeh et al 2013;Michail et al 2013) or fluorescence- (Higashi et al 2006;Zarghi et al 2010;Xie et al 2011;Puente et al 2011;Toker et al 2011;Hassan et al 2012;Tekkeli and Toker 2013) high performance liquid chromatography (HPLC) in pharmaceutical dosage forms and/or biological samples such as plasma/serum of animals and human. Although previous papers well reported validated data and practical applications including pharmacokinetic studies, most of previous studies likely focus on the development and validation of bio-analytical methods mostly using fluorescence-HPLC, even required by expensive and tedious sample preparations such as liquidliquid extraction or solid-phase extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Direct UV absorption and fluorescence analysis of memantine is challenging due to absence of chromophoric groups and the weak UV absorbance of the primary amine group. Derivatization reactions were proposed to impart measurable characteristics to mematine to enable UV, fluorescence and liquid chromatographic quantification [2][3][4][5][6][7][8][9][10]. Unfortunately, however, derivatization reactions involve highly reactive compounds that require high precautions and special safety measures.…”
Section: Introductionmentioning
confidence: 99%